The Roles of Self-esteem in the Relationship between Emotional Intelligence (EI) and Adjustment among International Students in Southern Thailand - Kim, Yejin; Dhammasaccakarn, Wanchai; Tongsamsi, Isara (UI Scholars Hub, 2021)
The main purpose of this research was to examine the potential mediation effects of self-esteem on the association between international students’ emotional intelligence (EI) and adjustment, as indexed by academic adjustment, social adjustment, and psychological adjustment. Data from 151 international students in southern Thailand were collected. The path analysis indicated that self-esteem fully mediated the relationships between EI and social adjustment and psychological adjustment, whereas self-esteem acted as a partial mediator between EI and academic adjustment. In addition, self-esteem impacted the three outcomes much more strongly than EI. Practical suggestions for enhancing students’ adjustment are addressed and examined. The limitations of the research and suggestions for further studies are also briefly discussed.